SPDSS demand in Malaysia - Abdullah, Alias; Abdul Samad, Dazilah; Ibrahim, Mansor; Abdullah, Muhammad Faris (2004)
This paper looks at the demand and interest for SPDSS among town planners in Malaysia. A survey was conducted among town planners registered with the Malaysian Institute of Planners and among local planning authorities. Based on the survey, it was found that many town planners in Malaysia are still unfamiliar with SPDSS. Nevertheless, they have expressed interest to know more about SPDSS as well as to include SPDSS in their work.